(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2016)
Swami Dayanand was the one who kept the love of freedom alive in hearts of Indians. He travelled throughout India to unite the people. Dayanand was fully convinced that only armed revolution could drive the British out of India. The real aim of Swami Ji was to unify India nationally, socially and religiously, he was the one who taught us the lesson of Swaraj and took it as birth right of men. Dayanand was democratic in his views and wanted general welfare of the countrymen. India has her own priceless heritage to offer to anybody who has anything to contribute to her regeneration thus Swami Dayanand’s views gave a new shape and creed to Indian Nationalism.